Characterization of teff straw from selected teff varieties from Ethiopia - Belete Tessema; Girma Gonfa; Sintayehu Mekuria Hailegiorgis; Venkatesa Prabhu Sundramurthy (Heliyon, 2023)
Utilization of biomass is important both for economic and environmental projection purposes. To use biomass for industrial applications as well as to reduce its pollution load on environment, it is important to characterize and determine the compositions of the biomass. In this work, the proximate and chemical analyses of straws of four (Dagim, Filagot, Kora and Kuncho) Teff (Eragrostis tef) varieties were investigated with three replications. The thermographic and FTIR of the teff straws and the ashes were also studied. The volatile matter contents of the teff straws were 78.80, 77.00, 80.20 and 80.60% for the Dagim, Kuncho, Kora and Filagot varieties, respectively. The ash contents of the straws were 6.34% for Dagim, Kuncho and Kora while the value is 6.00% for Filagot. The fixed carbon contents of the straws were 14.86, 16.67, 13.47 and 13.40% for Dagim, Kuncho, Kora and Filagot varieties, respectively. The silica contents of the teff straw for the Filagot, Kora, Dagim, and Kuncho varieties are 5.92, 5.66, 4.94, and 4.70%, respectively. This corresponds to 92.21, 91.59, 77.19 and 87.20% silica contents in the ashes produced from Filagot, Kora, Dagim, and Kuncho varieties, respectively. The results show that the proximate and chemical composition of ash produced from teff straws show slight differences. Moreover, the silica content of the teff straw is comparable with the values reported for rice husk and wheat straw. Thus, teff straw can be used for the production of silica.